MASSIVE CHROMITE IN THE BRENHAM PALLASITE AND THE FRACTIONATION OF CR DURING THE CRYSTALLIZATION OF ASTEROIDAL CORES - Wasson J.T.; Lange D.E.; Francis C.A.; Ulff-Moller F. (My University, 1999)
Large (=<2 mm) chromite grains are present in IIIAB iron meteorites and in the main-group pallasites (pmg), closely related to high-Au IIIAB irons. Pallasites seem to have formed by the intrusion of a highly evolved metallic magma from a IIIAB-like core into fragmented olivine of the overlying dunite mantle. High Cr contents are commonly encountered during the analyses of metallic samples of high-Au IIIAB irons and main-group pallasites, an indication that Cr contents were high in the intruding liquid and that Cr behaved as an incompatible element during the crystallization of the IIIAB magma, contrary to expectations based on the negative IIIAB Cr-Ni and Cr-Au trends among low-Au IIIAB irons.In a region about 10 cm across in the Brenham main-group pallasite massive chromite fills the interstices between olivine grains, the site normally occupied by metal in Brenham and other pallasites. The massive chromite may have formed as a late cumulus phase; because Fe-Ni was also crystallizing, its absence in the chromite-rich region suggests a separation associated with differences in liquid buoyancy. The coexisting chromite and olivine are zoned; in the olivine FeO is highest in pallasitic (olivine-metal) regions, lowest in rims adjacent to chromite, and intermediate in the cores of these olivines. Chromite shows the opposite zoning, with the highest FeO contents at grain edges adjacent to olivine. The observed gradients are those expected to form by Fe-Mg exchange between olivine and chromite during slow cooling at subsolidus temperatures. Compared to normal Brenham, contents of phosphoran olivine and phosphates are higher in the chromitic pallasitic region. We also report data for large-to-massive chromites present in pmg Molong and in high-Au IIIAB Bear Creek that, like Brenham, formed from a highly evolved magma. The Bear Creek chromite has a much lower Mg content than that in the pallasites, implying that, in the pmg, the Mg was extracted from the olivine during high-temperature reaction with the precipitating chromite. There are other circumstantial arguments indicating that Cr was incompatible in the metal during the crystallization of the IIIAB magma, with the concentration in the residual magma rising from an initial value of about 300 μg/g to a value around 700 μg/g when Bear Creek and Brenham were formed. We consider possible explanations for these negative Cr-Au and Cr-Ni trends and find the most probable one to be that they reflect sampling artefacts resulting from analysts avoiding visible chromite (and the commonly associated phase FeS) when choosing metal samples.